Effect of Electroacupuncture and Counseling on Sub-Threshold Depression: A Study Protocol for a Multicenter Randomized Controlled Trial - Wang, Xiaotong; Lin, Haixiong; Jiang, Xiumin; Ma, Minna; Shi, Dandan; Fan, Chun; Shao, Yin; Wu, Shengwei; Yu, Lin; Li, Danian; He, Jun; Chen, Yongjun (Frontiers in Psychiatry, 2020)
Background: Sub-threshold depression is common and could impair function, as well as increase the risk of developing major depression. Despite evidence of efficacy for electroacupuncture (EA) and counselling in the treatment of sub-threshold depression, the sample size is insufficient and the level of evidence remains low. This study aims to evaluate the effectiveness of sub-threshold depression treatments by comparing the treatment effects among EA, counselling, and combination therapy, as well as to further study their mechanism. Methods: This study is a multicenter, randomized, single blind clinical trial that will be conducted in settings at four clinical centers in China. The randomized controlled trial (RCT) will examine the effectiveness of EA intervention, compared with counselling and combination therapy. A total of 138 sub-threshold depression patients (18 to 55 years of age with Beck Depression Inventory (BDI-II) score≥14 points and Hamilton Depression Scale (HAMD-17) score: 7 points ≤ HAMD total score <17 points) will be recruited. The participants will be randomly assigned to receive the above treatments. The interventions will be delivered over a 6-week period (EA: 3 times a week for 6 weeks; 30 minutes a session. Counselling: once a week for 6 weeks; 50-60 minutes a session). The primary outcome measure will be the HAMD-17; BDI-II. The secondary outcome measures will be: Self-rating Depression Scale (SDS), Self-rating Anxiety Scale (SAS), and Pittsburgh Sleep Quality Index (PSQI). The assessments will occur at baseline, 2, 4, and 6 weeks and a follow-up period. Recruitment will commence in March 2020 and is anticipated to occur over a 2-year period. Discussion: This study intends to conduct a multicenter randomized controlled trial to compare the effectiveness among EA, counselling and the combined therapy in the treatment of patients with sub-threshold depression, and to further study the mechanisms of effect. Chinese Clinical Trial Registry registration number: ChiCTR1900028530.